2003
DOI: 10.1046/j.1365-2842.2003.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

An infection control protocol: effectiveness of immersion solutions to reduce the microbial growth on dental prostheses

Abstract: This investigation evaluated the effectiveness of an infection control protocol for cleansing and disinfecting removable dental prostheses. Sixty-four dentures were rubbed with sterile cotton swab immediately after they had been taken from patients' mouths. Samples were individually placed in the culture medium and immediately incubated at 37 +/- 2 degrees C. The dentures were scrubbed for 1 min with 4% chlorhexidine, rinsed for 1 min in sterile water and placed for 10 min in one of the following immersion sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
0
40

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(167 citation statements)
references
References 31 publications
7
120
0
40
Order By: Relevance
“…18,19,23,24 In fact, the results presented in the present study corroborated the findings in the literature, since, among the disinfecting solutions, 0.12% digluconate chlorhexidine presented the best results, reducing in 86% the number of microorganisms adhered to the surface of the specimens.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…18,19,23,24 In fact, the results presented in the present study corroborated the findings in the literature, since, among the disinfecting solutions, 0.12% digluconate chlorhexidine presented the best results, reducing in 86% the number of microorganisms adhered to the surface of the specimens.…”
Section: Discussionsupporting
confidence: 91%
“…4,[13][14][15] Thus, many studies have been performed with the objective of evaluating the efficiency of different disinfecting solutions in the control of Candida genus yeasts, searching for a disinfecting solution that would present excellent antimicrobial activity without harming the patient's health or causing alterations in the physical-structural characteristics of dentures. [16][17][18][19][20] Within this context, the objective of the present study was to evaluate the effect of sodium bicarbonate in the adherence of Candida albicans to thermally activated acrylic resin, comparing it to other disinfecting solutions already mentioned and tested in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen peroxide acts in chemical and mechanical way because during its degradation it promotes oxidation and oxygen release damaging the microbial cells and interfering with cell division 17 . Montagner et al showed that 10 v hydrogen peroxide solution was efficient against Candida albicans when used during 30 minutes 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The safety of the use of solutions as chlorhexidine, sodium hypochlorite, vinegar and hydrogen peroxide is reported in the literature [16][17][18][19][20][21][22][23][24] . They presented biocompatibility and low cytotoxicity when used in low concentrations being safe for denture chemical disinfection.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical characteristics such as rugosity, hardness, dimensional stability of color and bending properties can be changed after immersion in those solutions 1,11,13 .…”
Section: Introductionmentioning
confidence: 99%